Potency of Microalgae as Source of Functional Food in Indonesia (Overview) - Muhamad Maulana Azimatun Nur (Eksergi)
Malnutrition in Indonesia continues to increase. It is needed to develop functional food source that is capable to be produced in rapid, feasible, sustainable, and meets the nutritional needs for the country. Microalgae is a type of single-celled plants, live in water by using photosynthesis to produce biomass. Microalgae such as Spirulina platensis has a high protein content. It also contains vitamins and pigments that is useful to the body. The potential of microalgae production in Indonesia is high considering that Indonesia passed the equator and has a supporting environment. Trends in the future, it is expected Indonesia could produce microalgae at high mass scale, at a cheap price and can be applied in everyday life.